Role of proadrenomedullin in the progression of diabetic kidney disease in patients with type 2 diabetes mellitus - A.M. Urbanovych; A.P. Vereshchynska (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. Type 2 diabetes mellitus (T2DM) is a chronic disease with increasing prevalence. Metabolic changes and inflammation caused by hyperglycemia in T2DM lead to deterioration of kidney function. Diabetic kidney disease (DKD), a common complication of T2DM, is a leading cause of end-stage renal disease. We investigated the prognostic value of proadrenomedullin (Pro-ADM) as an unconventional biomarker of renal impairment progression in patients with T2DM. The purpose was to investigate the role of proadrenomedullin in the progression of DKD in people with T2DM. Materials and methods. Eighty-six patients with T2DM and DKD were examined. The study was conducted at the Lviv Regional State Clinical Medical and Diagnostic Endocrinological Center, a clinical base of the Department of Endocrinology of the Danylo Halytsky Lviv National Medical University. Patients were divided into 3 groups according to the degrees of DKD risk progression. In addition to standardized clinical and laboratory tests, the concentration of Pro-ADM in blood serum was evaluated. The obtained data were processed statistically with an assessment of probability and correlation. Results. The level of Pro-ADM in patients with T2DM and DKD varied statistically significant depending on the risk of DKD progression. In group 1, its average content was 19.65 ± 0.98 pmol/l, in group 2 — 35.15 ± 2.46 pmol/l, and in group 3 — 72.02 ± 2.82 pmol/l. The results showed a significant increase in Pro-ADM with DKD progression (p < 0.001). A correlation analysis was performed between Pro-ADM and patients’ age, duration of disease, HbA1c, total cholesterol, urea, creatinine, estimated glomerular filtration rate (eGFR) levels, and albumin-creatinine ratio (ACR). In group 1, a positive weak correlation was found between Pro-ADM and age (R = 0.02; p < 0.01); cholesterol (R = 0.03; p > 0.05); urea (R1 = 0.17; p < 0.01); creatinine levels (R = 0.12; p < 0.01); and ACR (R = 0.16; p < 0.01). There was a positive moderate correlation with the duration of T2DM (R = 0.39; p < 0.05) and HbA1c level (R = 0.31; p < 0.05) and a moderate negative correlation with eGFR (R = –0.51; p < 0.01). In group 2, a positive weak correlation of Pro-ADM with age (R = 0.12; p < 0.01); duration of T2DM (R = 0.28; p < 0.05); cholesterol (R = 0.06; p > 0.05), and urea levels (R = 0.06; p > 0.05) was observed. There was a positive moderate correlation with HbA1c (R = 0.31; p < 0.05); creatinine (R = 0.47; p < 0.01) levels, and ACR (R = 0.32; p < 0.01). A moderate inverse correlation with eGFR was also found (R = –0.33; p < 0.01). In group 3, a positive weak correlation of Pro-ADM with the duration of T2DM (R = 0.24; p < 0.05), and total cholesterol level (R = 0.19; p > 0.05) was observed. A positive moderate correlation with age (R = 0.53; p < 0.01); HbA1c (R = 0.33; p < 0.05), urea (R = 0.42; p > 0.05), creatinine levels (R = 0.34; p < 0.01), and ACR (R = 0.36; p < 0.01) was found. There was also a negative strong correlation with eGFR (R = –0.71; p < 0.01). Conclusions. We found a significant increase in Pro-ADM level in patients with T2DM depending on the progression of DKD. The revealed correlations between Pro-ADM and clinical parameters of T2DM and the functional state of the kidneys indicate that the level of Pro-ADM is associated with the progression of DKD. These results show the importance of identifying Pro-ADM as a potential marker for assessing the progression of renal impairment in patients with T2DM.